Frequency of metabolic syndrome in women treated at the Menopause Clinic of the “Dr. José Eleuterio González” University Hospital of the UANL in Northeastern Mexico - Cervantes Flores, Maribel; Vázquez Méndez, Juana; Saldívar Rodríguez, Donato; Vidal Gutiérrez, Oscar; González Carrillo, I. Y.; Guerrero González, Geraldina (UANL. Facultad de Medicina, 2014)
Objectives: To determine the frequency of metabolic syndrome (MS) in patients with menopause, and to compare the incidence of MS between surgical and natural menopause. Methods: This was an observational, longitudinal, descriptive, retrospective, unblinded study of cases seen at the Menopause Clinic of the University Hospital “Dr. José eleuterio González” of the Universidad Autónoma de Nuevo León from March 2009 to December 2011. The frequency of MS was determined based on Adult Treatment Panel III (ATPIII) classiication. Results: at the end of the study, 391 patients were evaluated. The mean age was 50.1 years. We found a frequency of MS of 38.1%, the risk factor most often found was low HDL-cholesterol (62.5%), followed by obesity (46.5%), hypercholesterolemia (42.3%), hyperglycemia (11.5%), and hypertension (7.7%). The incidence of natural and surgical menopause was 37.6% vs. 39.2% respectively; however, the result was not statistically signiicant (p = 0.093). Conclusions: Patients with menopause are at increased risk of developing MS. it is important to detect MS early in this of patients, when they have one risk factor to avoid complications which may trigger the syndrome. We recommend screening for MS during perimenopause, in order to detect and try to delay it in a timely manner and recommend primary prevention (diet and exercise), or secondary prevention in cases with one or more risk factors.